2001
DOI: 10.1161/01.hyp.37.6.1429
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive Drugs Influence Aortic Augmentation Index Independently of Pulse-Wave Velocity in Healthy Men

Abstract: Abstract-Aortic augmentation index, a measure of central systolic blood pressure augmentation arising mainly from pressure-wave reflection, increases with vascular aging. The augmentation index is influenced by aortic pulse-wave velocity (related to aortic stiffness) and by the site and extent of wave reflection. To clarify the relative influence of pulse-wave velocity and wave reflection on the augmentation index, we studied the association between augmentation index, pulse-wave velocity, and age and examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
236
5
7

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(272 citation statements)
references
References 36 publications
24
236
5
7
Order By: Relevance
“…However, this positive correlation was not found after adjustment for age in a previous study. 36 Moreover, this relation implies that the coefficient and the sites of reflection are stable, which was probably not the case in our study because of the extensive arthrosclerosis and regional modifications of vascular resistance inherent in heart failure. 37 As previously reported, 21 we found regional heterogeneity of arterial stiffening according to EF status, probably partly because of the marked increase in proximal arterial stiffness associated with age.…”
Section: Discussionmentioning
confidence: 59%
“…However, this positive correlation was not found after adjustment for age in a previous study. 36 Moreover, this relation implies that the coefficient and the sites of reflection are stable, which was probably not the case in our study because of the extensive arthrosclerosis and regional modifications of vascular resistance inherent in heart failure. 37 As previously reported, 21 we found regional heterogeneity of arterial stiffening according to EF status, probably partly because of the marked increase in proximal arterial stiffness associated with age.…”
Section: Discussionmentioning
confidence: 59%
“…38 Nitrate administration decreases SBP and AIx via a reduction in vascular tone of small arteries independently from aortic PWV. 39 In a previous study, we showed that acute WBV attenuated the increases in reflected wave magnitude, aSBP, leg PWV and baPWV during metaboreflex-induced sympathetic activation following a continuous 4 min session of static squat, suggesting that vibration-related factors induced functional sympatholysis in the legs. 22 In the current study, WBV training decreased the sympathovagal balance (LFnu/ HFnu) due to a concurrent decrease in sympathetic (LFnu) and increase in cardiovagal (HFnu) modulation.…”
Section: Discussionmentioning
confidence: 76%
“…18,19 Other studies reported that augmentation index was correlated to both SBP and DBP 20 or only to SBP. 21,22 Interestingly, Cameron et al 21 found in a study population of 262 hypertensive subjects that augmentation index was correlated to DBP only in males and that this relation was lost when augmentation index was normalised for age.…”
Section: Introductionmentioning
confidence: 97%